How Literacy and Savings Link Digital Finance to Sustainability? - Efriyani Sumastuti; C.Tri Widiastuti; Ika Indriasari; Antono Herry Purnomo Adhi (Economics Development Analysis Journal, 2026)
This study analyzes how digitalization, financial inclusion, and financial literacy affect business savings and the sustainability of culinary Micro, Small, and Medium Enterprises (MSMEs) in Central Java, Indonesia. Data from 210 MSME owners were examined using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that digitalization and financial inclusion significantly increase business savings, thereby enhancing MSME sustainability. Financial literacy does not directly affect sustainability but moderates the relationship between savings and sustainability, strengthening the effectiveness of savings utilization. The model shows strong explanatory power, with R² values of 0.37 for business saving and 0.90 for sustainability. The Importance–Performance Map Analysis identifies financial literacy and digitalization as highly important yet moderately performing variables, marking them as priorities for policy development. Overall, the findings highlight that MSME sustainability in Central Java depends on integrating digital finance, inclusive access, and sound saving behavior, supported by financial literacy. The study provides policymakers and financial institutions with practical insights for designing integrated digital finance and literacy programs that strengthen MSME resilience and regional economic growth.